Faktor-Faktor yang Memengaruhi Harga Saham pada Bisnis Subsektor Makanan dan Minuman yang Terdaftar di IDX - Aang Syahdina; Sarah Nurjanah; Warjudin Warjudin; Moh. Magfirah Dillah Syaid; Jordan Ismadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to investigate the effects of the Current Ratio (CRA), Debt-to-Equity Ratio (DERA), and Return on Equity (ROEQ) on the stock prices (HS) of companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period from 2017 to 2022. The analysis utilizes data sourced from the published annual financial statements of the relevant companies, employing a purposive sampling method to select 17 companies from the food and beverage subsector as the research sample. This research employs a quantitative descriptive approach and multiple linear regression analysis processed with Eviews Version 12. The findings indicate that CRA does not have a significant effect on stock prices when analyzed separately. Conversely, ROEQ has a positive and significant impact on stock prices, while DERA shows a significant negative effect. These findings affirm that the three variables, namely CRA, DERA, and ROEQ, contribute to stock price fluctuations both individually and collectively. Therefore, this research recommends that companies in the food and beverage sector enhance their financial performance, particularly through better debt management and increased profits, in order to strengthen the attractiveness of their stock prices in the market and attract greater interest from investors.